An investigation of targeted inhibition of transcription factor activity with pyrrole imidazole polyamide (PA) in chronic myeloid leukemia (CML) blast crisis cells. Issue 18 (15th September 2019) - Hayatigolkhatmi, K.; Padroni, G.; Su, W.; Fang, L.; Gómez-Castañeda, E.; Hsieh, Y.C.; Jackson, L.; Pellicano, F.; Burley, G.A.; Jørgensen, H.G.
Graphical abstract: Abstract: Tyrosine kinase inhibitor (TKI) therapy is the standard treatment for chronic phase (CP)-chronic myeloid leukemia (CML), yet patients in blast crisis (BC) phase of CML are unlikely to respond to TKI therapy. The transcription factor E2F1 is a down-stream target of the tyrosine kinase BCR-ABL1 and is up-regulated in TKI-resistant leukemia stem cells (LSC). Pyrrole imidazole polyamides (PA) are minor groove binders which can be programmed to target DNA sequences in a gene-selective manner. This manuscript describes such an approach with a PA designed to down-regulate E2F1 controlled gene expression by targeting a DNA sequence within 100 base pairs (bp) upstream of the E2F1 consensus sequence. Human BC-CML KCL22 cells were assessed after treatment with PA, TKI or their combination. Our PA inhibited BC-CML cell expansion based on cell density analysis compared to an untreated control after a 48-hour time-course of PA treatment. However, no evidence of cell cycle arrest was observed among BC-CML cells treated with PA, with respect to their no drug control counterparts. Thus, this work demonstrates that PAs are effective in inhibiting E2F1 TF activity which results in a temporal reduction in BC-CML cell number. We envisage that PAs could be used in the future to map genes under E2F1 control in CML LSCs.